A Novel Germ-Line Point Mutation in RET Exon 8 (Gly533Cys) in a Large Kindred with Familial Medullary Thyroid Carcinoma - Álvares Da Silva, Adriana M.; Maciel, Rui M. B.; Dias Da Silva, Magnus R.; Toledo, Silvia R. C.; De Carvalho, Marcos B.; Cerutti, Janete M. (The journal of clinical endocrinology and metabolism, 2003)
Familial medullary thyroid carcinoma is related to germ-line mutations in the RET oncogene, mainly in cysteine codon 10 or 11, whereas noncysteine mutations in codons 13–15 are rare. We now report a new missense point mutation in exon 8 of the RET gene (1597G→T) corresponding to a Gly533Cys substitution in the cystein-rich domain of RET protein in 76 patients from a 6-generation Brazilian family with 229 subjects, with ascendants from Spain. It is likely that the mutation causes familial medullary thyroid carcinoma (FMTC), because no other mutation was found in RET, the mutation cosegregates with medullary thyroid carcinoma (MTC) or C cell hyperplasia (CCH) in patients subjected to surgery, and family members without the mutation are clinically unaffected. The histological analysis of 35 cases submitted to thyroidectomy revealed that 21 patients had MTC after the age of 40 yr and 8 before the age of 40 yr, 4 presented MTC or CCH before the age of 18 yr, 2 died due to MTC at the age of 53 and 60 yr, and CCH was found in a 5-yr-old child, suggesting a clinical heterogeneity. To improve the diagnosis of FMTC, analysis of exon 8 of RET should be considered in families with no identified classical RET mutations.